METHODOLOGY FOR BUILDING A TEXT-STRUCTURE ORIENTED LEGAL CORPUS - ONESTI, Cristina (Comparative Legilinguistics, 2011)
The present study aims at showing the methodology for building a legal corpus with a special attention paid to the internal structure of legal documents and juridical texts. Built at the University of Turin, the Corpus Jus Jurium tries to cover the entire legal universe current in contemporary Italy, whose life is represented from their first conception in the parlamentary discussion, to their codification in normative rules, to their application in judgements. The Corpus Jus Jurium will be lemmatized, POS-tagged and have added a textual markup, casting some light on the still neglected textual expression of legal and juridical texts, which is decisive for every national legal system. Elaborating texts with such peculiarites implies a long amount of manual work. However, the final result can be an extremely useful resource for translators looking for idioms, collocations or terminological elements in specific parts of texts and for forensic linguists, providing them with an extensive repository of well-structured data and with fine-grained querying opportunities, whether at the morphosyntactic or lexical or textual level.